Next-Generation Sequencing for Non-Ampullary Duodenal Carcinoma Suggesting the Existence of an Adenoma-Carcinoma Sequence - Yoshida, Tsubasa (Case Rep Gastroenterol, 2021)
Duodenal tumors with a sporadic adenoma-carcinoma sequence are extremely rare. For such clinically suspected cases without a specific family history, performing a comprehensive gene search is important to understand the germline mutation background. We present a 68-year-old woman without a genetic or familial history of familial adenomatous polyposis (FAP), Peutz-Jeghers syndrome, or Lynch syndrome who presented to Kosei Hospital, Japan, with exertional dyspnea induced by abdominal pain lasting 3 weeks. A duodenal tumor was suspected by contrast-enhanced computed tomography. Esophagogastroduodenoscopy showed a lesion accompanied by a white microprotuberance on the descending part of the duodenum opposite the papilla, with a giant ulcerative lesion at the center of the white lesion. Biopsy revealed a low-grade adenoma, high-grade adenoma, and adenocarcinoma. Immunohistochemical analysis of the adenoma and adenocarcinoma showed Ki-67, p53, cytokeratin 20, caudal-type homeobox 2, and carcinoembryonic antigen positivity and cytokeratin 7 negativity. The findings suggested the presence of an adenoma-adenocarcinoma sequence in duodenal carcinoma. However, in the mutational analysis using next-generation sequencing, c.4348C>T (p.Arg1450Ter) mutation in APC was detected in all normal mucosal, adenoma, and carcinoma tissues. This mutation is common in FAP patients. Even if the presence of an adenoma-adenocarcinoma sequence in duodenal carcinoma is suggested in cases without a familial FAP history, as in this case, genetic analysis may reveal FAP. Thus, performing a comprehensive genetic analysis of duodenal carcinoma patients with a possible adenoma-carcinoma sequence is necessary to explore their genetic background.